Analisis Putusan Mahkamah Konstitusi Nomor:137/PUU-XIII/2015 Tentang Pembatalan Kewenangan Gubernur dalam Pembatalan Peraturan Daerah Kabupaten/Kota - Bonadi, Ahmad; Syafa'at, Rachmad; Sudarsono, Sudarsono (Universitas Negeri Malang, 2019)
This paper aims to analyzes the consideration of Constitutional Court judges in canceling Article 251 paragraph (2), paragraph (3), paragraph (4) and paragraph (8) of the Republic of Indonesia Law No. 23 of 2014 concerning Regional Autonomy and the impact of the Constitutional Court Decision Number: 137 / PUU-XIII / 2015. The study uses normative legal research with a statute approach, conceptual approach, and case approach. The decision of the Constitutional Court judges in deciding their cases is based on the principles of constitutionalism, the principle of the unitary state of the Republic of Indonesia, the principle of regional autonomy and decentralization, and the principle of judicial power and rule of law. The impact of the Constitutional Court Ruling Number: 137/PUU-XIII/2015 is the increased burden of the case of material testing rights in the Supreme Court, the abolition of the governor’s authority to cancel district/city regulations, and hinder the deregulation program to accelerate development.